Descriptive sensory analysis of virgin and refined, bleached, deodorized coconut oil - Dy, Lianne Marsha M.
ABSTRACT Sensory profiles of virgin coconut oil (VCO) from different processes and the refined, bleached, deodorized (RBD) coconut oil were obtained using descriptive analysis (DA). The generated sensory terms include: yellow color; turbidity; acid, coco jam, latik, nutty and rancid aroma; sweetness; saltiness; and coco jam, latik, margarine, nutty and rancid flavor. Results showed that samples were significantly different (p ≤ 0.05) in all attributes except for turbidity and margarine flavor. RBD coconut oil had no other perceptible attribute except for its distinct yellow color and slight salty taste. All VCO samples had slightly perceptible sweetness and nutty flavor. The heated VCO samples had distinct acid aroma, coco jam and latik attributes, while the fermented, non-heated VCO sample had intense rancid attributes. Significant correlation (R^2 ≥ 0.60) was found between the coco jam and latik attributes, sweetness and coco jam flavor, and acid aroma and rancid flavor.